KRISIS PANDEMI COVID-19: DAMPAKNYA PADA PENDAPATAN DAERAH DARI SEKTOR PERPAJAKAN DAN RETRIBUSI - Syamsul, Syamsul; Nurlailah, Nurlailah; Nurhadi, Nurhadi (KEUNIS, 2022)
This study aims to analyze the impact of the COVID-19 pandemic on regional income from the tax and retribution sector. This research was conducted on 34 provincial governments in Indonesia. The type of quantitative data is the realization of regional taxes and retribution for the 2019 and 2020 fiscal years. Furthermore, the data are analyzed using descriptive and quantitative techniques. The results of the descriptive analysis show that during the COVID-19 pandemic there was a decrease in regional income from regional taxes and retribution, which almost occurred in all provinces in Indonesia. Similarly, the results of the analysis of the different test, paired samples t test also inform the occurrence of differences in income obtained from regional taxes and retribution before and during the COVID-19 pandemic. In other words, the existence of the COVID-19 pandemic has an impact on regional income from the regional tax and the retribution sector in Indonesia. This information is useful for policy makers in making decisions regarding the impact of the COVID-19 pandemic on regional income from the regional tax and retribution sector.